ANALYSIS OF PATIENT SATISFACTION AT OUTPATIENT PHARMACY USING SERVQUAL METHOD: STUDY AT X HOSPITAL JAKARTA. - Daniar Pratiwi; Djoko Wahyono; Sampurno Sampurno (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Currently, Indonesia’s health development began to emphasize on improving the quality of health care, where service quality should be oriented to customer satisfaction. Departement of Pharmacy at X Hospital Jakarta is one of the medical support required todeliver a quality service that oriented to patient satisfaction. This research was descriptive study using primary data that obtained from the questionnaire that distributed to 400 patients at outpatient pharmacy, which was the patient who secured by insurance (A and B) and cash (F). The category of patients at outpatient pharmacy are patient that secured by corporate, corporate pensioner in Jabodetabek, patient that secured by other insurance and cash patient. The sampling technique used is nonprobability sampling, which was the quota sampling. The level of satisfaction of patients seen by SERVQUAL method and the dimension of service quality was mapped in a Cartesian Diagram.In general, patients were not satisfied with the performance of Outpatient Pharmacy at X Hospital Jakarta. The results showed that the gap between patients’ expected service and perceived service of outpatient pharmacy at X Hospitals was negative. The sequence of the biggest negative gap felt in responsiveness (-0.7100), empathy (-0.6550), reliability (-0.5800), assurance (-0.4975) and tangible (-0.4200). The sequence of the greatest dissatisfaction felt by corporate pensioner in Jabodetabek (30.59%), cash patients (29.08%), patient that secured by other insurance (22.22%) and patient that secured by corporate (18.11%). The sequence of the biggest dissatisfaction perceived by the patient for services in outpatient pharmacy F (37.49%), outpatient pharmacy A (32.47%) and outpatient pharmacy B (30.04%). Based on the mapping of Cartesian Diagram, Outpatient Pharmacy at X Hospital Jakarta should pay more attention to the dimensions of responsiveness, especially regarding speed of service and providing more crew at peak hours.Keywords: Quality of Service, Satisfaction, SERVQUAL, Cartesian Diagram